2021
DOI: 10.1186/s12913-020-05876-1
|View full text |Cite
|
Sign up to set email alerts
|

Discovering healthcare provider behavior patterns through the lens of Medicare excess charge

Abstract: Background The phenomenon of excess charge, where a healthcare service provider bills Medicare beyond the limit allowed for a medical procedure, is quite common in the United States public healthcare system. For example, in 2014, healthcare providers charged an average of 3.27 times (and up to 528 times) the allowable limit for cataract surgery. Previous research contends that such excess charges may be indicative of the actual amount that providers bill to non-Medicare patients and subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Additionally, we could not capture unmet needs among parents (ie, those who had MH needs but did not seek MH services), and we lacked data on enrollee race and ethnicity, income, and cancer stage, which may be important factors associated with MH care needs and merit future investigation. The observed rural-urban differences in MH care utilization among mothers may be associated with the differential billing behaviors of providers in rural areas, a factor we were unable to measure …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we could not capture unmet needs among parents (ie, those who had MH needs but did not seek MH services), and we lacked data on enrollee race and ethnicity, income, and cancer stage, which may be important factors associated with MH care needs and merit future investigation. The observed rural-urban differences in MH care utilization among mothers may be associated with the differential billing behaviors of providers in rural areas, a factor we were unable to measure …”
Section: Discussionmentioning
confidence: 99%
“…The observed rural-urban differences in MH care utilization among mothers may be associated with the differential billing behaviors of providers in rural areas, a factor we were unable to measure. 56 …”
Section: Discussionmentioning
confidence: 99%
“…9 A greater CMAA ratio may represent higher cost, greater physician market power, or cost-shifting to recoup underpayment from Medicare from higher-paying private insurers. 17 To estimate patient volume, we calculated the number of total Medicare patient visits by summing the number of unique patients for the following HCPCS codes: 99201, 99202, 99203, 99204, and 99205 for new patients; 99211, 99212, 99213, 99214, and 99215 for return patients. 10 We excluded payments to radiation oncologists or pathologists due to the lack of specificity for urologic services.…”
Section: Claims Datamentioning
confidence: 99%
“…9 However, a lower CMAA may also reflect a reduced need to cost-shift, in which providers attempt to recoup underpayment from public payers in higher prices to commercial payers, due to a higher proportion of commercially insured patients. 6,17 We have previously shown that PE-backed urology practices have lower rates of Medicaid acceptance compared to non-PE practices, however, further examination of payer mix is needed to elucidate the drivers behind differences in CMAA ratio. 24 This study has several limitations.…”
Section: Commentmentioning
confidence: 99%